Profil Peserta Olimpiade Matematika dalam Konstruksi Soal Cerita - Rofidatul Azizah (Institut Agama Islam Negeri (IAIN) Tulungagung, 2019)
Mathematical problems expressed in the form of verbal or story problems are felt difficult by some students. Constructing verbal form questions or story problems should be able to be trained to students in the learning process in the classroom, so that they are trained in dealing with problems while providing experience in solving various problems faced or mathematical problems. This study aims to describe the profile of mathematics olympiad participants in the construction of story problems. The results of the study show that the ability of students in the mathematics Olympiad to construct the story problem is that students of the Olympic Games can reformulate the problem in constructing the story problem based on the information provided, he can also reconstruct the problem in the story problem by modifying the information provided without changing the intent of the information provided and they are also able to complete the construction of the problem by using a completion procedure, and are able to imitate the problem in constructing the problem of the story by linking it in real life and assuming the initial problem or information provided as the first step in solving a new problem.